2020
DOI: 10.1002/jmrs.421
|View full text |Cite
|
Sign up to set email alerts
|

A review of the barriers to using Patient‐Reported Outcomes (PROs) and Patient‐Reported Outcome Measures (PROMs) in routine cancer care

Abstract: Introduction: Patient-reported outcomes (PROs) are direct reports from patients about the status of their health condition without amendment or interpretation by others. Patient-reported outcome measures (PROMs) are the tools used to measure PROs; they are usually validated questionnaires patients complete by self-assessing their health status. Whilst the benefits of using PROs and PROMs to guide real-time patient care are well established, they have not been adopted by many oncology institutions worldwide. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
134
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(167 citation statements)
references
References 41 publications
(145 reference statements)
4
134
0
Order By: Relevance
“…The electronic capture and utility of PROMs has transformed the evaluation of health outcomes in surgical research, partly due to well-defined surgical pathways and time points during the preoperative baseline to postoperative recovery and rehabilitation [ 12 , 16 ]. However, the adoption of PROMs in clinical practice is limited by the burden placed on patients to interpret and complete surveys, is often restricted to the clinical encounter, and associated with several administrative and logistical barriers in sustaining longitudinal data collection, especially in busy, resource-limited settings [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The electronic capture and utility of PROMs has transformed the evaluation of health outcomes in surgical research, partly due to well-defined surgical pathways and time points during the preoperative baseline to postoperative recovery and rehabilitation [ 12 , 16 ]. However, the adoption of PROMs in clinical practice is limited by the burden placed on patients to interpret and complete surveys, is often restricted to the clinical encounter, and associated with several administrative and logistical barriers in sustaining longitudinal data collection, especially in busy, resource-limited settings [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts should now be focused on the implementation of routine remote ePRO monitoring as part of the peri-surgical pathway. One of the main barriers in implementing ePRO is the clinicians' knowledge to meaningfully interpret and integrate PRO data into their clinical practice 16 ; therefore, research such as this from Avery and colleagues is pivotal for benchmarking and in addressing these issues. Ultimately, the potential use of ePROs collected for routine individual monitoring will also help in evaluating and improving thoracic surgery service quality on a population level.…”
mentioning
confidence: 99%
“…8 Together, the three papers discussed here make a compelling case for health services to consider implementing PROs. For centres which have not yet adopted ePRO systems, a very pragmatic starting point is to undertake an assessment of their local barriers, guided by the Nguyen et al 4 review, and involve staff at all levels within the centre in workshops to identify potential strategies to address barriers. Another important factor with PRO implementation is considering whose role it is to administer and act upon PROs.…”
mentioning
confidence: 99%
“…A critical first step to supporting oncology institutions to implement and use PROs in routine care is to fully understand the barriers to this occurring. In their literature review of 14 eligible studies, Nguyen et al 4 identified barriers at the patient, health professional and service levels. As detailed in their paper, the patient barriers include time, incapacity, and difficulty using electronic devices to report their outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation